2012
DOI: 10.1080/02705060.2011.644702
|View full text |Cite
|
Sign up to set email alerts
|

Round goby predation onDreissenain coastal areas of eastern Lake Michigan

Abstract: Predator-prey interactions between round goby (Neogobius melanostomus) and Dreissena are an important component of the food web in their invaded range in North America and Europe. We conducted two experiments to test the effect of round goby predation on Dreissena in coastal lakes connected to eastern Lake Michigan, USA. First, we conducted a density gradient experiment using 1-m 2 cages stocked with 0 to 15 large round gobies (individuals 4 7.5 cm total length (TL)). Presence of large round gobies significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…This was interesting, as the introduced round goby is one of the few fish species known to consume molluscs, although only predation on non‐native species ( D. polymorpha and C. fluminea ) has been documented (Brandner, Auerswald, Cerwenka, Schliewen, & Geist, ). Nonetheless, the introduced round goby has potential to have direct impacts on native unionid mussels, and on juveniles in particular; however, predation from various predator groups on abundant non‐native mussels has been commonly reported (Kipp, Ricciardi, & Ramcharan, ; Ruetz, Reneski, & Uzarski, ).…”
Section: Discussionmentioning
confidence: 99%
“…This was interesting, as the introduced round goby is one of the few fish species known to consume molluscs, although only predation on non‐native species ( D. polymorpha and C. fluminea ) has been documented (Brandner, Auerswald, Cerwenka, Schliewen, & Geist, ). Nonetheless, the introduced round goby has potential to have direct impacts on native unionid mussels, and on juveniles in particular; however, predation from various predator groups on abundant non‐native mussels has been commonly reported (Kipp, Ricciardi, & Ramcharan, ; Ruetz, Reneski, & Uzarski, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Great Lakes, the appearance of zebra mussel depleted populations of the amphipod Diporeia, which forced Lake Whitefish and Alewives to shift their prey use; feeding success declined, as did growth rate and condition (Madenjian et al 2015;Pothoven et al 2001;Pothoven and Madenjian 2008). Some fishes incorporate zebra mussels into their diets (French and Bur 1996;Nack et al 2015;Pothoven et al 2001;Ruetz et al 2012;Watzin et al 2008), but we found no evidence of early stage Striped Bass feeding on zebra mussel veligers. Other molluscs occurred as rare prey in Striped Bass and other early-stage fishes in our samples; thus we regard as possible but unlikely that the absence of young bivalves in our samples might be attributable to preservation in formalin.…”
Section: Discussionmentioning
confidence: 55%
“…Overall, our eDNA data identified statistically significant positive species co‐occurrences in both rivers (Figure b). Only the RG eDNA data showed one positive co‐occurrence with Common Carp in the Grand River, a species that is also fairly common throughout the river and was also observed to feed on dreissenids, the diet of RG (Ruetz, Reneski, & Uzarski, ).…”
Section: Discussionmentioning
confidence: 99%